Dielectrophoresis and colloidal phase transitions for ultra-broadband optical limiting - Rittirong Nuansri; Prathan Buranasiri; H. Daniel Ou-Yang; Ivan Biaggio (My University, 2019)
We demonstrate wavelength-independent optical limiting based on colloidal phase transitions induced by the dielectrophoretic force from focused electromagnetic radiation. The focused radiation acts as an optical trap that increases the particle density. The increased density then leads to a colloidal gas-solid phase transition and an aggregate that effectively blocks the incoming radiation when it passes a threshold power. The process is reversible, with the colloidal particles returning to a homogenous distribution after the incoming radiation is removed. We demonstrate the effect using polystyrene nanoparticles mixed with pluronics and polyethylene glycol polymers in low-concentration KCl salt solutions. We observe the light-induced phase separation under confocal fluorescent microscope, and we provide a proof-of-principle demonstration of optical limiting using a 100 μm thick colloid cell.
Keywords: Polystyrene; Orbital Angular Momentum in Optics